ANALISIS PERENCANAAN PENGELOLAAN KEUANGAN DESA MENURUT PERATURAN MENTERI DALAM NEGERI NOMOR 113 TAHUN 2014 (Studi Kasus di Desa Masangan Wetan Kecamatan Sukodono Kabupaten Sidoarjo Periode 2017) - Wiwin Deri Fitriani; Jeni Susyanti; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of this study is analize village financial management planning according to Permendagri Number 113 in 2014 case study on Masangan Wetan village Sukodono district, Sidoargo Regency. This study used descriptive qualitative as a methods to village officials relate to village financial management planning.The result in this study condude that the village financial management process on Masangan Wetan village, Sukodono district, Sidoarjo regency is in accordance with Permendagri Number 113 in 2014.Keywords: Financial Management Planning, Village Officials, Ministry of Home Affairs Regulation